Train Network Control System and Its Fault Diagnosis of Guangzhou Metro Line 3 - HUANGWen-can (机车电传动)
Taking Guangzhou metro line 3 as an example, train network control system and its diagnosis were analyzed. Based on the Guangzhou metro line 3 train network control system troubleshooting and analysis, higher requirements of the train network control system stability was put forward.